Plectrosternus Lacordaire, 1857 (Coleoptera: Elateridae); genus new to northern Western Ghats, India with a description of one new species - Patwardhan, Amol; Athalye, R. P. (Zootaxa, 2012)
A new species Plectrosternus foveatus sp.nov. is described and illustrated. This is the first record of the genus from northern Western Ghats (Type locality: Yeoor, Thane, Maharashtra, India) and the third species from India.